Long-Term Signs of T Cell and Myeloid Cell Activation After Intestinal Transplantation With Cellular Rejections Contributing to Further Increase of CD16+ Cell Subsets - Stobutzki, Nadja; Schlickeiser, Stephan; Streitz, Mathias; Stanko, Katarina; Truong, Kim-Long; Akyuez, Levent; Vogt, Katrin; Appelt, Christine; Pascher, Andreas; Blau, Olga; Gerlach, Undine A.; Sawitzki, Birgit (Frontiers in Immunology, 2019)
The intestine mediates a delicate balance between tolerogenic and inflammatory immune responses. The continuous pathogen encounter might also augment immune cell responses contributing to complications observed upon intestinal transplantation (ITx). We thus hypothesized that ITx patients show persistent signs of immune cell activation affecting both the adaptive and innate immune cell compartment. Information on the impact of intestinal grafts on immune cell composition, however, especially in the long-term is sparse. We here assessed activated and differentiated adaptive and innate immune subsets according to time, previous experience of cellular or antibody-mediated rejections or type of transplant after ITx applying multi-parametric flow cytometry, gene expression, serum cytokine and chemokine profiling. Independent of previous rejections ITx patients showed an increase in CD16 expressing monocytes and myeloid dendritic cells (DCs) in comparison to healthy controls, which was even detectable in patients who were transplanted more than 10 years ago. Also, conventional CD4+ and CD8+ T cells showed persistent signs of activation, which was counterbalanced by increased activated CCR4+ regulatory T cells. Patients with previous cellular rejections had even higher proportions of CD16+ monocytes and DCs, whereas transplanting higher donor mass with multi-visceral grafts was associated with increased T cell activation. The persistent inflammation and innate immune cell activation might contribute to unsatisfactory results after ITx.